The genetic mechanisms and inheritance of the polled, scur and horn phenotypes of South African Bonsmara cattle - Van Marle-Koster, Este (University of Pretoria, 2022)
Thesis (PhD Animal Science (Animal Breeding and Genetics))--University of Pretoria, 2022.